Convalecent - Hyperimmune Plasma Use and Immunological Charachteristics in the Covid-19 Pandemic: A Preliminary Experience of a Single Center in Italy as Fast Available Therapy Model in New Virus Pandemic - Caimmi, Philippe Primo; Mascaro, Gennaro (British Journal of Healthcare and Medical Research, 2024)
Objectives: Hyperimmune - convalescent plasma transfusion appears to be a great resource in the current SARS-CoV-2 coronavirus pandemic and seems to be one of the few effective treatment modality available. However, its efficacy is variable and dependent on antibody/plasma volume concentration. Methods & Results: This single center analysis from a forefront COVID-19 Italian hospital in 43 convalescent plasma donors demonstrated that this variability in neutralizing antibody (NAB) levels is related to the harvesting period after SARS-CoV-2 recovery and interestingly, on blood group type. Specifically, the optimal plasmaferesis time point was approximately two weeks post test negativation with a significant drop in NAB plasma levels (112±102 vs 60±26.9, p=0.003) observed at 30 days. In contrast, no correlation between NAB and IgG plasma levels was observed over time (r=0.48.). Subgroup analyses demonstrated that NAB levels where higher in male (115.1±110.7, p=0.0001) and in blood group AB (200±138.6, p=0.036) donors while group A patients (81.2±82.7, p=0.062) had the lower levels of NAB concentration. Conclusion: This analysis demonstrated that male patient with a AB blood group plasma which was donated within three weeks of convalescence contains the highest therapeutic levels of antibodies and these patients should be actively recruited to become donors.